Projeto e caracterização de molécula fotônica com três anéis acoplados para aplicações em sensoriamento - Saraiva, Nathan Gonzaga (2024)
Photonic devices based on resonant cavities in the form of rings are capable of confining energy in the form of light, generating numerous applications such as compact optical sensors with high sensitivity. These cavities can be coupled forming an architecture with two or more rings, called Photonic Molecule (PM), in order to tune the resonances of the spectral response that no longer depend on the characteristics of a single cavity, breaking the intrinsic dependence between cavity radius, free spectral range and total quality factor, allowing compact and robust devices. In line with the immediate need to develop high sensitivity sensors and compact devices with low power consumption, this work aims to employ the unique properties of PMs and use a device with three coupled cavities, two of which are coupled inside an external cavity, which in turn is coupled to a waveguide. This PM will be simulated, fabricated and characterized on a silicon-on-insulator (SOI) platform, using standard-sized waveguides (450nm x 220nm), an outer ring with 20m radius and inner rings with equal radius of 9.4375m. The coupling distances between the inner rings and the outer ring must be equal to 150nm and the coupling distances between the outer ring and the waveguide buses must be equal to 200nm. This architecture will guarantee the generation of a spectrum that allows light to travel both clockwise and counterclockwise within the chip, increasing the possibilities of spectral control. As for application, detection windows opened over some specific regions of the PM will be used to guarantee displacements of resonances when light interacts with any target analyte positioned in these windows.